Renewable Transport: How Renewable Energy and Electric Vehicles using Vehicle to Grid Technology can make Carbon Free Urban Development. - Newman, Peter; Went, A.; Wal, J. (2008)
Renewable Transport is proposed as the phrase to describe a new collection of technologies based on V2G, PHEVs and Smart Grids. Vehicle to Grid (V2G) is the idea that the combined electrical storage capacity in a fleet of Plug-in Hybrid Electric Vehicles (PHEVs), linked through a smart grid, can allow the introduction of a large amount of renewable energy into the electricity network. This paper discusses the individual benefits of each of the technologies required for Renewable Transport, then how their combination can lead to even greater reductions in fossil fuel consumption and greenhouse gas emissions. The payback period for the electric vehicle’s initial price premium is estimated from fuel savings and income generated by providing ancillary services to electric utilities. Further, the number of vehicles required for a given penetration of wind power providing baseload electricity is assessed. It also discusses the current advances in these technologies and makes suggestions on how it can be implemented in a carbon free development demonstration project from the perspective of the Western Australian electricity network.